Clonidine p-isothiocyanate, an affinity label for alpha 2-adrenergic receptors on human platelets. - Atlas, D (1982)
Exposure of intact human platelets or platelet membranes to the clonidine analog clonidine p-isothiocyanate (clonidine-NCS), followed by extensive washing, results in the loss of [3H]yohimbine binding to platelet alpha 2-receptors. In addition, exposure of intact platelets to clonidine-NCS, followed by extensive washing, results in the loss of of epinephrine-induced inhibition of adenylate cyclase activity [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] in frozen--thawed platelets and in purified platelet membranes. This effect is dependent on time and concentration (t 1/2 at 30 degrees C is less than 15 min; half-maximal effect occurs with clonidine-NCS at less than 10 microM). Clonidine-NCS appears to interact by irreversibly blocking the platelet alpha 2-receptors because (i) it abolishes alpha 2-receptor effects of adenylate cyclase activity (i.e., epinephrine-induced inhibition of basal and prostaglandin E1-stimulated activity) while not altering other cyclase activity (basal, prostaglandin E1-stimulated, and NaF-stimulated) and (ii) its effect on both [3H]yohimbine binding and epinephrine-induced inhibition of adenylate cyclase can be specifically prevented by alpha-agonists [(-)-epinephrine and clonidine] and alpha-antagonists (yohimbine and phentolamine). These observations indicate that clonidine-NCS is an effective affinity label for platelet alpha 2-receptors.